TO STUDY THE EFFICACY OF TROPICAL APPLICATION OF CANNABIS IN CHRONIC KNEE JOINT PAIN PATIENTS - URVASHI GANGWAL; JAIDEEP SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objective of this study was to study the decrease in pain at specified time intervals after tropical application of cannabis oil in chronic joint pain patients and to study the change in the visual analog score (VAS) and numeric rating scale (NRS) scoring of patient’s pain before and after the application. Methods: Patients were pre-informed about the process. VAS and NRS scores were noted before tropical application of the Cannabis oil. Cannabis oil was applied tropically on patients with chronic joint pain on the specified site, that is, B/L knee joints. Then, the decrease in the severity of pain at specific time interval was recorded on the pre-set pro forma. The VAS score and NRS score were recorded 30 min after the application. The final data were represented in the form of tables and graphs. Results: The mean improvement values at 0–5 min, 5–10 min, 15–20 min, and 20–30 min were 35.90%, 41.80%, 47.90%, and 56.50%, respectively. The mean VAS score before application 7.00 reduced significantly to 2.32 after 30 min of application (p<0.05). Similarly, the mean NRS score also reduced significantly to 2.52 from mean value 7.08 at before application (p<0.05), that is, pain is significantly reduced. Conclusion: From the data analysis, we reach to the conclusion that tropical application of Cannabis oil is effective in B/L knee joint osteoarthritis chronic pain.